2022
DOI: 10.3389/fncel.2022.926453
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Microglia/Macrophages Activation and TLR4/NF-κB/MAPK Pathway in Distraction Spinal Cord Injury-Induced Inflammation

Abstract: Distraction spinal cord injuries (DSCIs) often occur as the neurological complication of distraction forces following the implantation of internal fixation devices during scoliosis correction surgery. However, the underlying mechanism behind these injuries remains unclear. The present study aimed to explore the activation of microglia and macrophages, as well as changes in TLR4-mediated NF-κB and MAPK pathway activity after DSCIs in Bama miniature pigs. Prior to surgical intervention, the pigs were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…In this study, GSS was found to decrease the high expression of GFAP and GBP2 after HIE in neonatal rats, indicating depressive effects of activation and A1-type polarisation on astrocytes. CD16 is one of the markers of microglial polarisation into the M1 type after activation [ 49 , 50 ]. GSS also reduced the transcription of both CD11b and CD16 mRNA as well as the protein level of CD11b, showing an inhibitory effect on the activation and polarisation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, GSS was found to decrease the high expression of GFAP and GBP2 after HIE in neonatal rats, indicating depressive effects of activation and A1-type polarisation on astrocytes. CD16 is one of the markers of microglial polarisation into the M1 type after activation [ 49 , 50 ]. GSS also reduced the transcription of both CD11b and CD16 mRNA as well as the protein level of CD11b, showing an inhibitory effect on the activation and polarisation of microglia.…”
Section: Discussionmentioning
confidence: 99%
“…They believed that spinal anomalies, particularly structural kyphosis, rapidly arise as a result of subcortical osteolytic lesions in asymmetrical vertebral locations. Additionally, a severe pathological fracture and an intra-spinal haematoma can compress the spinal cord and nerves, resulting in myelopathy and weakening of the paravertebral muscles ( 8 , 12 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a classical in ammatory pathway, TLR4/NF-κB has received growing interest in the study of POCD [10][11]. TLR4, a toll-like receptor, is a type I transmembrane type protein widely distributed in brain neurons, microglia and astrocytes [12]. Lipopolysaccharide (LPS) is a speci c exogenous ligand for TLR4, which can bind to the receptor TLR4 and activate the MyD88-dependent pathway as a downstream signaling to transduce in ammatory signals and also activate NF-κB (nuclear factor kappa B) [13][14].…”
Section: Introductionmentioning
confidence: 99%